Bahá'í Faith: Its History and Teachings, The by William Miller: "Missionary as Historian: William Miller and the Bahá'í Faith" - Martin,Douglas (Baha'i Studies, 1978)
Lengthy review of Miller's book, and a broad discussion of anti-Bahá'í polemic and historiography.
To clarify: This 1978 review is titled "Missionary as Historian: William Miller and the Bahá'í Faith." It is a review of the book titled The Bahá'í Faith: Its History and Teachings (1974).
Keywords: Christian missionaries; Christianity; Criticism and apologetics; Douglas Martin; William McElwee Miller